Association of APOE e2 genotype with Alzheimer’s and non-Alzheimer’s neurodegenerative pathologies - Terry E. Goldberg (Nature Portfolio, 2020)
The apolipoprotein E (APOE) gene contains both the major common risk variant associated with clinically diagnosed late onset Alzheimer’s disease (AD), APOE e4, and a neuroprotective variant, APOE e2. Here the authors confirm that the e2 allele is protective against Alzheimer’s disease neuropathologies, but show that it is not protective against other neurodegenerative disorders.